An Analysis of Errors in the Acquisition of Modal Particles by Thai Chinese Learners- Based on the Comparative Analysis of Modal Particle in Chinese and Thai - Rakkiattiyod, Kamontip (Journal of Human and Society, Sisaket Rajabhat University, 2022)
From the perspective of Chinese teaching and investigation, modal particle was a kind of speech. This paper was concerned with the comparison of Chinese and Thai semantic functions and an analysis the errors of Chinese modal particles for four types. The errors were summed up: omission, wrong addition, wrong substitution and dislocation, and finally we discuss teaching strategies of the errors. The results of this research can enhance the ability and development of Chinese teaching in Thailand.